Ductile shear zones (Chapter 2) - Pamplona, J. (2020)
Tabular or sheetlike and planar or curviplanar zones in which rocks are more highly strained than rocks adjacent to the zone are called ductile shear zones. The identification and study of ductile shear zones (Figures 2.1–2.73) are important, because such shear zones define major plate boundaries. We need to study such zones because along them, partially molten rocks can flow. Second, viscous dissipation related to such zones has been investigated. No slip boundary condition was assumed classically to explain the kinematics of ductile shear zones. However, recently, the slip boundary condition has become more recognised. The ductile shear sense/sense of movement from such zones can be deciphered mainly from asymmetric sigmoid, parallelogram and lenticular clasts as well as intrafolial folds. In addition to such shear sense indicators, this chapter also presents near symmetric clasts that form possibly within shear zones but that do not give the shear sense.